Hematological and Biochemical Study in Children Infected with Entamoeba histolytica in Al Diwaniyah Province/Iraq - Abdul-Ameer, Al-Anbaki Ali; Azizi, Al-Badri Mokhalad; Habeeb, Al-Asady Suaad Mudhaher (Central Asian Journal of Medical and Natural Science, 2025)
Abstract: Intestinal parasitic infections, especially Entamoeba histolytica, are a serious public health problem worldwide, especially in developing countries, particularly Iraq. The current study aimed to estimate the correlation between E. histolytica infection in children and some hematological and biochemical parameters . Ninety clinically ill patients presented to the Women and Children's Hospital with contaminated diarrhea between September 2024 and March 2025. Patients' ages ranged from 5 to 13 years. Stool samples were collected from 90 individuals for direct microscopic examination . Stool samples were obtained from 90 participants for direct microscopic analysis. Out of these, 60 individuals were diagnosed with E. histolytica infection, while the remaining 30 healthy individuals formed the control group. Body mass index (BMI) and hematological markers, including erythrocytes, hemoglobin level, packed cell volume (PCV), white blood cell count (WBC), neutrophils, and lymphocytes, were assessed using a Sysmex analyzer. The results showed a significant decrease (P < 0.05) in body mass index (BMI) , the red blood cell (RBCs) , hemoglobin level, and packed cell volume (PCV) in patients diagnosed with an E. histolytica infection compared to the healthy control. The study revealed that patients infected with E. histolytica showed a marked increase (P<0.05) in total white blood cell (WBC) count, neutrophil count, and lymphocyte count when compared to the healthy group . Biochemical parameters, including C-reactive protein (CRP) and kidney function (urea and creatinine), were significantly elevated (P<0.05) in the E. histolytica infected group compared with the healthy control, In contrast , lipid profile, cholesterol, and triglyceride levels were significantly lower (P<0.05) in comparison to the healthy group. The study concluded that there is an correlation between E. histolytica infected and changes in hematological and biochemical parameters, leading to anemia and immune system disorders. The kidneys and liver are also affected, resulting in impaired lipid metabolism and digestion.